Hughes syndrome/APS - Hughes, Graham (Henry Stewart Talks, 2017)
Hughes syndrome/APS: past, present & future, APS: not just thrombosis and miscarriage, β2 GP1, Sleep disturbance & APS, Teenage migraine, Genetics vs. environment, Pain in the hips, MS or APS?, Infertility, "Funny turns": epilepsy, Fainting in school: APS and PoTS, Unhelpful tests, The big 3: Hughes syndrome, Sjogren’s syndrome and Hashimoto’s, Predictions for 2050